Some string Bianchi type III cosmological models for perfect fluid distribution in general relativity - Amirhashchi, Hassan; Zainuddin, Hishamuddin; Hassan, Jumiah; Mohamed Kamari, Halimah (Ibnu Sina Institute for Fundamental Science Studies, Universiti Teknologi Malaysia, 2010)
The present study deals with Bianchi type III string cosmological models with perfect fluid distribution of matter. To get the deterministic models of the universe, the expansion (ᶿ) in the model is assumed to be proportional to the shear (σ). This leads to condition A = Bn, where A and B are metric potentials and n is a constants. We discuss the physical and geometrical behaviour of these models in two cases: (i) P-String (ρ = (1 + ω)λ) and (ii) Reddy String (ρ + λ = 0), where ρ and λ are the rest energy density and the tension density of the string cloud, respectively and ω ≥ 0.